A Serıal Extractıon Case Whıch Requıred Enucluatıon Of Upper Second Premolars As A Result Of Ectopıc Eruptıon - İlken Kocadereli; Ayhan Enacar (Galenos Yayinevi, 1993)
A serial extraction case which had skeletal Class I properties is presented. Instead of rutin applications the enucluation of maxillary second premolars did not effect the stability of the orthodontic result.